2020
DOI: 10.1101/2020.06.14.150649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Growth Rate Hypothesis as a predictive framework for microevolutionary adaptation to selection for high population growth: an experimental test under phosphorus rich and phosphorus poor conditions

Abstract: Type of article: Letters Number of words in Abstract: 145 Number of words in Main text: 4897Number of words in Text box: 0 Number of references: 86 Number of Figures: 3 in main text; 5 in appendix Number of Tables: 1 in main text; 9 in appendixAuthorship: KDL and SAJD developed the idea and designed the experiments. KDL carried out the experiments assisted by LZ and performed the data analysis. SP analyzed the microsatellite data. KDL and SAJD wrote the first drafts of the manuscript, and all authors contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 77 publications
3
4
0
Order By: Relevance
“…Our Papakostas et al, 2016;Paraskevopoulou et al, 2020Paraskevopoulou et al, , 2018Zhang et al, 2019). On the other hand, they support earlier conclusions that these species do hybridize (Lemmen et al, 2020;Papakostas et al, 2016) providing a plausible explanation for frequently observed mitonuclear discordances in field populations (Papakostas et al, 2016;Zhang et al, 2019). The mate competition experiment shows that intraspecific fertilizations are more likely to occur than interspecific fertilizations.…”
Section: Discussionsupporting
confidence: 89%
“…Our Papakostas et al, 2016;Paraskevopoulou et al, 2020Paraskevopoulou et al, , 2018Zhang et al, 2019). On the other hand, they support earlier conclusions that these species do hybridize (Lemmen et al, 2020;Papakostas et al, 2016) providing a plausible explanation for frequently observed mitonuclear discordances in field populations (Papakostas et al, 2016;Zhang et al, 2019). The mate competition experiment shows that intraspecific fertilizations are more likely to occur than interspecific fertilizations.…”
Section: Discussionsupporting
confidence: 89%
“…Alternatively, the benign nature of the HP common garden environment may have masked subtle trade-offs. Intriguingly, a similar pattern in performance has been observed in several other studies that have used common garden experiments to compare the fitness of LP-and HP-adapted populations (Declerck et al, 2015;Frisch et al, 2014;Lemmen et al, 2020).…”
Section: Rapid Heritable Adaptation In Response To Exposure To Low and High Phosphorus Resourcessupporting
confidence: 75%
“…Alternatively, the benign nature of the HP common garden environment may have masked subtle trade-offs. Intriguingly, a similar pattern in performance has been observed in several other studies that have used common garden experiments to compare the fitness of LP-and HP-adapted populations (Declerck et al 2015;Frisch et al 2014;Lemmen et al 2020). The lack of difference may also be attributed to the fact that generation times of populations fed with phosphorus rich food are considerably shorter than with phosphorus poor food (Zhou et al 2018), and that non-genetic phenotype modifications tend to degrade across generations after the removal of the environmental trigger (Herman et al 2014;Houri-Ze'evi & Rechavi, 2017).…”
Section: Effect Of Exposure Histories In Hp Common Garden Treatmentsupporting
confidence: 70%